Ethnocentrism, Social Identification, and Discrimination - Perreault, Stéphane; Bourhis, Richard Y. (Personality & social psychology bulletin, 1999)
In line with social identity theory (SIT), minimal group paradigm (MGP) studies have shown that high in-group identifiers discriminate more than low in-group identifiers. But why do some people identify more to their ad hoc group in the MGP? One week prior to a MGP study, 121 undergraduates completed scales assessing their ethnocentrism, authoritarianism, and personal need for structure. In Phase 2, the same participants took part in a MGP study in which us-them categorization was either assigned randomly or was chosen. Participants who chose their group membership identified more with their own group and discriminated more than respondents randomly assigned to their group. Path analysis showed that ethnocentrism and perception of control over group ascription predicted degree of in-group identification, which in turn, was positively related to discriminatory behavior.